2013
DOI: 10.1002/app.39180
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of phosphorylated nata‐de‐coco for polymer electrolyte membrane applications

Abstract: Fuel cells are being developed to overcome the global energy crisis. The objective of this research is to prepare an environmental‐friendly and cheap material as the polymer electrolyte membrane. Coconut water was fermented by Acetobacter xylinum to produce nata‐de‐coco and the phosphorylation was carried out by microwave‐assisted reaction. The resulting membranes are characterized by ion exchange capacity, contact angle, proton conductivity, swelling index, methanol permeability, mechanical properties measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
3
17
0
2
Order By: Relevance
“…-O δ-will also interact with other protonated water molecules leading to increased proton transfer and increasing the conductivity of the phosphorylated nata de coco membrane. Intermolecular interaction between polymer chains will fall and interaction between phosphate groups and water will subsequently rise [13]. The average value of ΔE, ΔG and ΔH for the interaction between water molecule and nata de coco dimer increased gradually at addition of 1-2 water molecules, decreased gradually up to addition of five water molecules, and were relatively constant for the next addition of water molecules.…”
Section: Proton Transfer and Hydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…-O δ-will also interact with other protonated water molecules leading to increased proton transfer and increasing the conductivity of the phosphorylated nata de coco membrane. Intermolecular interaction between polymer chains will fall and interaction between phosphate groups and water will subsequently rise [13]. The average value of ΔE, ΔG and ΔH for the interaction between water molecule and nata de coco dimer increased gradually at addition of 1-2 water molecules, decreased gradually up to addition of five water molecules, and were relatively constant for the next addition of water molecules.…”
Section: Proton Transfer and Hydrationmentioning
confidence: 99%
“…This is consistent with previous research suggesting that proton dissociation is tied to the proportion of water and phosphoric acid in the system; phosphorylated nata de coco is comprised of hydrophobic and hydrophilic domains allowing proton transfer to occur through cluster networks. With water in the media, a balance between protons and hydroxyl ions is established [13]. The bonding energy tends to be similar, with a rise in bonding energy corresponding to increased hydration.…”
Section: Proton Transfer and Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of membranes which have a potential to be used in PEMFC is phosphorylated nata de coco membrane. Studies' findings showed that proton conductivity of phosphated nata de coco membrane is almost close to Nafion 117's conductivity which is of 1.20 x 10 -2 S/cm [14]. Nata de coco is selected for this study since it relatively spends low cost, easily to obtain and has good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hydrophilic and sulfonic group can form intramolecular and intermolecular hydrogen bonding. The ability of electrolyte membrane to take water will determine its ability to conduct proton [17].…”
Section: Introductionmentioning
confidence: 99%